IMPLEMENTASI SISTEM PENDAFTARAN ELEKTRONIK PASIEN LAMA DI TPPRJ RUMAH SAKIT BHAYANGKARA TK III HOEGENG IMAN SANTOSO BANJARMASIN - Nor Latifah; Muhammad Rashif Anshari (JEMPOL : Jurnal Elektronik Mahasiswa Polanka, 2023)
The administration of medical records in the patient reception (registration) section has now developed. The development that can be seen in health services, especially in hospitals, such as the patient reception or registration section. The purpose of this study is to find out the implementation of the Electronic Registration System for Existing Patients at TPPRJ Bhayangkara Hospital in Banjarmasin. This study uses a descriptive qualitative method with data collection techniques using interviews with 5 informants and observation. The results of the study for the man aspect found that the quantity of human resources was sufficient and the quality of human resources was also in accordance with the specified standards. For the machines aspect, the facilities and infrastructure (hardware) used at TPPRJ are very good and the amount of hardware provided is very sufficient for the current implementation of electronic registration. The software used is SIMRS Isena. In the methods aspect, there are Standard Operating Procedures (SOP) available for electronic patient registration. Based on the results of the study, it can be concluded that the implementation of the electronic registration system for the man aspect, in terms of quantity and quality, has been fulfilled and is appropriate. For the machines aspect, related hardware and software are available, and in the methods aspect, there are already SOPs.